Morphological changes in sperm cells during epididymal transit in West African dwarf buck (2000)
The spermatozoa characteristics during epididymal transit were studied .in healthy West African dwarf (WAD) goat bucks. The caput epididymis had a value of 27.0% of abnormal sperm cell, which is significantly different (P<0.05) from the 21.0% of corpus and 23.0% of the cauda epididymis. There was no significant difference (P>0.05) between the values of corpus and caudal epididymis. The caput epididymis also had 6.0% spermatozoa with proximal cytoplasmic droplets which differed significantly (P<0.05) from that of the corpus (1.20%) and the cauda (0.9%), The values for coiled tails and tire total abnormal sperm cells showed that caput epididymis had higher abnormal spermatozoa, which was closely followed by cauda while the corpus epididymis had the least. There were more spermatozoa with looped tails in the cauda epididymis (1.68%) than in other segment (corpus: 0.95% and caput: 0.80%). The testicular and epididymal parameters were positively correlated (weight of testis and epididymis; weight of testis, scrotal circumference, testicular circumference, weight of epididymis and weight of testis (r = >0.05) except the correlation values between length of epididymis and length of tests (r = 0.30).